Impact of dental anxiety on quality of life in patients undergoing endodontic and restorative care - Darmadi, Eveline Yulia; Fauziah, Yessy Andriani; Yemy Ameliana; Dwi Setianingtyas; Wahjuningrum, , Dian Agustin (Conservative Dentistry Journal, 2025)
Background: Dental anxiety is a common psychological condition that affects individuals undergoing conservative dental procedures such as root canal therapy and restorative treatments. It influences not only a patient’s decision to seek care but also their perception of treatment outcomes and overall quality of life related to oral health. Purpose: This literature review aims to evaluate the relationship between dental anxiety and oral health, particularly its impact on the quality of life of patients undergoing endodontic and restorative dental treatments. Reviews: Dental anxiety is closely associated with increased pain perception, reduced cooperation, and decreased trust in dental professionals. Patients with high anxiety often experience greater discomfort and dissatisfaction, reflected in difficulties eating, speaking, and socializing. Studies consistently show that anxiety can impair treatment experiences and outcomes, while proper management leads to improved oral health and well-being. Effective strategies such as clear communication, empathetic interaction, and adequate pre-treatment preparation are proven to reduce fear and enhance patient satisfaction.Conclusion: Dental anxiety has a significant effect on many aspects of a patient's well-being before, during, and after conservative dental procedures. By adopting a caring and personalized approach, dental professionals can help alleviate anxiety and support improved treatment experiences and outcomes.